Short- and long-glass fibre reinforced polyamide 6,6 composites: Tensile properties of injection moulded specimens - Hassan, Aziz; Yahaya, A, Hamid; Ibrahim, Z, Abidin; P. R, Hornsbry, (Malaysian Journal of Science, 2001)
Injection moulding of fibre reinforced polymer composites is associated with the problem of fibre breakage. If fibre length retained in the finish product is too short, this will limit the expected improvement in property and defeat the purpose of reinforcement. Extrusion and pultrusion are two methods normally employed for the melt compounding of polymer composite feed stock for the injection moulding, produced short- and long-fibre composites, respectively. ln this work, these composites were injection moulded at different fibre loading and tested for the tensile properties. Both tensile strength and tensile modulus of long fibre composites improved compared to the short composites counterpart despite reduction in fracture strain.